PROBLEMATIKA KURIKULUM MERDEKA PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR - Ferytama, Ayu; Mutiah, Masayu; Ardila, Ayu; Tasya Jadidah, Ines (Pimpinan Cabang Muhammadiyah Kramat Jati, 2023)
This research aims to describe the challenges of the independent curriculum in the science subject (IPAS) at elementary schools. The method used in this research is qualitative descriptive. Data collection techniques include interviews through Google Forms and document analysis. The results of this research highlight the importance of the independent curriculum in the current era, methods of implementing the independent curriculum in science learning, challenges specific to the social studies component of science education at the elementary school level, and solutions to address these challenges. One of the challenges in implementing the independent curriculum in the science subject is related to planning and execution, where some teachers still lack a complete understanding of the independent curriculum itself. To overcome this, teachers seek more information or references regarding assessment learning by reading materials related to the independent curriculum, drawing inspiration from teachers who are content creators, and regularly participating in training or seminars organized by the school or other educators.